Pengaruh Agresivitas Pelaporan Keuangan Terhadap Agresivitas Pajak (Studi Kasus Sub Sektor Pertambangan Yang Terdaftar Di Bursa Efek Indonesia Tahun 2017-2018) - Baiq Fira Damayanti; Meta Ardiana (JFAS : Journal of Finance and Accounting Studies, 2022)
Inflation that occurs in the mining sector is an unusual thing for companies, which causes companies to manipulate financial reports and taxes issued. The management of this sector is not transparent enough so that the potential revenue for the state is not optimal. This is influenced by tax payments Thisstudy aims to examine how the influence offinancial reporting aggressiveness on taxaggressiveness. In this study, data sourced from thefinancial statements of mining companieslisted in the Indonesian StockExchange for the 2017-2018period are used. Thesample used by researchers was 24 companies. The typeof research used isquantitative research with a descriptive statistical approach. Testing the hypothesis used in the study is simple linear regression.The results of this studyindicate that the aggressiveness offinansial reporting has a partial efect on tax aggressiveness Keywords: Descretionary accruel ; Effective tax rate ; tax aggressiveness ; financial reporting aggressiveness